Dexmedetomidine preconditioning protects against lipopolysaccharides-induced injury in the human alveolar epithelial cells - Zhang,Lei (2017)
Abstract Background and objectives Dexmedetomidine (DEX) has demonstrated the preconditioning effect and shown protective effects against organize injury. In this study, using A549 (human alveolar epithelial cell) cell lines, we investigated whether DEX preconditioning protected against acute lung injury (ALI) in vitro. Methods A549 were randomly divided into four groups (n = 5): control group, DEX group, lipopolysaccharides (LPS) group, and D-LPS (DEX + LPS) group. Phosphate buffer saline (PBS) or DEX were administered. After 2 h preconditioning, the medium was refreshed and the cells were challenged with LPS for 24 h on the LPS and D-LPS group. Then the malondialdehyde (MDA), superoxide dismutase (SOD), Bcl-2, Bax, caspase-3 and the cytochrome c in the A549 were tested. The apoptosis was also evaluated in the cells. Results Compare with LPS group, DEX preconditioning reduced the apoptosis (26.43% ± 1.05% vs. 33.58% ± 1.16%, p < 0.05) in the A549, which is correlated with decreased MDA (12.84 ± 1.05 vs. 19.16 ± 1.89 nmoL.mg-1 protein, p < 0.05) and increased SOD activity (30.28 ± 2.38 vs. 20.86 ± 2.19 U.mg-1 protein, p < 0.05). DEX preconditioning also increased the Bcl-2 level (0.53 ± 0.03 vs. 0.32 ± 0.04, p < 0.05) and decreased the level of Bax (0.49 ± 0.04 vs. 0.65 ± 0.04, p < 0.05), caspase-3 (0.54 ± 0.04 vs. 0.76 ± 0.04, p < 0.05) and cytochrome c. Conclusion DEX preconditioning has a protective effect against ALI in vitro. The potential mechanisms involved are the inhibition of cell death and improvement of antioxidation.